Protein-bound solute removal during extended multipass versus standard hemodialysis - Eloot, Sunny (BMC Nephrol, 2015)
BACKGROUND: Multipass hemodialysis (MPHD) is a recently described dialysis modality, involving the use of small volumes of dialysate which are repetitively recycled. Dialysis regimes of 8 hours for six days a week using this device result in an increased removal of small water soluble solutes and middle molecules compared to standard hemodialysis (SHD). Since protein-bound solutes (PBS) exert important pathophysiological effects, we investigated whether MPHD results in improved removal of PBS as well. METHODS: A cross-over study (Clinical Trial NCT01267760) was performed in nine stable HD patients. At midweek a single dialysis session was performed with either 4 hours SHD using a dialysate flow of 500 mL/min or 8 hours MPHD with a dialysate volume of 50% of estimated body water volume. Blood and dialysate samples were taken every hour to determine concentrations of p-cresylglucuronide (PCG), hippuric acid (HA), indole acetic acid (IAA), indoxyl sulfate (IS), and p-cresylsulfate (PCS). Dialyser extraction ratio, reduction ratio, and solute removal were calculated for these solutes. RESULTS: Already at 60 min after dialysis start, the extraction ratio in the hemodialyser was a factor 1.4-4 lower with MPHD versus SHD, resulting in significantly smaller reduction ratios and lower solute removal within a single session. Even when extrapolating our findings to 3 times 4 h SHD and 6 times 8 h MPHD per week, the latter modality was at best similar in terms of total solute removal for most protein-bound solutes, and worse for the highly protein-bound solutes IS and PCS. When efficiency was calculated as solute removal/litre of dialysate used, MPHD was found superior to SHD. CONCLUSION: When high water consumption is a concern, a treatment regimen of 6 times/week 8 h MPHD might be an alternative for 3 times/week 4 h SHD, but at the expense of a lower total solute removal of highly protein-bound solutes.